Analysis of The Standard Quality of The Crude Solar Salt become The Health and Industry's Salt in Karawang District - Pasaribu, Roberto Patar; Pranoto, Aris Kabul; Tanjung, Anasri; Waluyo, Waluyo; Suratna, Suratna (PELAGICUS, 2022)
"Krosok" salt, or "Crude Solar Salt", is salt produced through the evaporation and crystallization of seawater. Some krosok salts have different qualities, and this is influenced by the quality of seawater as raw material, available production facilities and post-harvest handling. This krosok salt is mainly produced by salt farmers along the north coast of Karawang Regency. This study aimed to determine the quality of krosok salt obtained from salt farmers in Karawang Regency and to raise salt quality standards to increase the sale value of salt by creating healthy and industrial salt products. The method is to re-crystallize the "krosok" salt by adding binders or additives. Based on the results of the salt crystal test in the laboratory, it is known that the crystallization of "krosok" salt in Karawang Regency has a NaCl content of up to 99.35%; this value is already above the SNI quality standard of 98% as health salt. Meanwhile, for hazardous materials such as (Hg) and (As), the content is around 0.001%, below the SNI threshold of 0.1%.